Universal nature of the saddle states of structural excitations in metallic glasses. (March 2021) - Ding, J.; Li, L.; Wang, N.; Tian, L.; Asta, M.; Ritchie, R.O.; Egami, T.
Abstract: A widely used schematic picture of the potential energy landscape (PEL) for liquid and glass gives an impression that the pathway of moving from a valley to another through a saddle point is predetermined. However, in reality the pathway is much more stochastic and unpredictable because thermal history is wiped out at the saddle point and the pathway down is randomly chosen. Here we explain this puzzling behavior through the study of local structural evolutions in the β relaxation process by atomistic simulations of structural excitations for metallic glasses. We find that the saddle states in the PEL show universal melt-like features in short-range order and atomic dynamics, independent of thermal history and composition. We propose that the short-lived local melting at the saddle point is responsible for wiping out the prior thermal history. This explains why the activation and relaxation stages of the β process are decoupled. The findings highlight the importance of understanding the nature of the saddle states in elucidating the system dynamics, and pose a question on the current view on the system evolution in the PEL. Highlights: In the potential energy landscape (PEL) picture, the pathway from one minimum to the next appears to be predetermined. However, earlier studies have showed that the choice of the pathway is highly stochastic in the PEL. We have found this is because the system locally melts for a short time at the saddle point, wiping out the memory. Therefore, the interpretation of the PEL needs to be modified.